2017
DOI: 10.1016/j.rmcr.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Switching from sildenafil to riociguat for the treatment of PAH and inoperable CTEPH: Real-life experiences

Abstract: Riociguat is a novel soluble guanylate cyclase stimulator that is approved for the treatment of patients with pulmonary arterial hypertension (PAH) and patients with inoperable chronic thromboembolic pulmonary hypertension (CTEPH) or persistent/recurrent CTEPH after pulmonary endarterectomy (PEA). As riociguat is a relatively new drug, experience of its use in clinical practice is limited, especially in patients who would not have met the inclusion criteria for the pivotal Phase III clinical trials, PATENT-1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
6
0
4
Order By: Relevance
“…AEs were rarely reported during the treatment-free period, and during the dose-adjustment period, only one patient discontinued riociguat, and 11 patients experienced AEs that resulted in dose reduction or interruption. Although it is important to interpret these observations with caution based on the inherent selection bias of a retrospective chart review (discussed below), they are in line with the results of published case studies and retrospective analyses of both PAH and CTEPH patients switching from other PH-targeted therapies (mainly PDE5i) to riociguat in real-world clinical practice [ 18 , 20 , 42 45 ]. The results from CAPTURE also support preliminary data from the RESPITE clinical trial, which indicated that switching from sildenafil or tadalafil to riociguat in patients with PAH not reaching treatment goals was safe and well tolerated [ 25 ].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…AEs were rarely reported during the treatment-free period, and during the dose-adjustment period, only one patient discontinued riociguat, and 11 patients experienced AEs that resulted in dose reduction or interruption. Although it is important to interpret these observations with caution based on the inherent selection bias of a retrospective chart review (discussed below), they are in line with the results of published case studies and retrospective analyses of both PAH and CTEPH patients switching from other PH-targeted therapies (mainly PDE5i) to riociguat in real-world clinical practice [ 18 , 20 , 42 45 ]. The results from CAPTURE also support preliminary data from the RESPITE clinical trial, which indicated that switching from sildenafil or tadalafil to riociguat in patients with PAH not reaching treatment goals was safe and well tolerated [ 25 ].…”
Section: Discussionmentioning
confidence: 53%
“…This strategy of switching patients from one PH-targeted therapy to another is largely unexplored in clinical practice. Small studies and case reports have demonstrated positive outcomes after switching, but these have largely involved switching within a drug class, and were mainly due to lack of efficacy [ 18 20 ] or safety and tolerability [ 21 , 22 ] of the former drug.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, a systematic review and meta-analysis by Becattini, consisting of 543 papers, analysed the efficacy of bosentan for CTEPH, 22 and found that it may improve haemodynamic response and probably exercise capacity in patients with CTEPH. Some studies also showed that a PDE5i, such as sildenafil, 2335 could be useful in improving symptoms and long-term function in CTEPH patients. Different studies of CTEPH patients yield different results regarding the effect on cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial NO synthase expression, NO production and NO availability are substantially reduced in patients with PAH, 5,10 so the sGC stimulator may be effective in patients who have not sufficiently responded to a PDE5 inhibitor. [34][35][36] The recent open-label, uncontrolled, phase…”
Section: Sgc Stimulatormentioning
confidence: 99%